Balloon catheter dilatation versus probing as primary treatment for congenital dacryostenosis. Issue 5 (9th October 2010) - Goldich, Yakov; Barkana, Yaniv; Zadok, David; Avni, Isaac; Pras, Eran; Mezer, Eedy; Morad, Yair
Abstract : Aim: To compare the success rate of balloon catheter dilatation of the nasolacrimal duct with probing and irrigation as primary treatment for congenital dacryostenosis. Methods: Charts of all children who were operated on for the first time for congenital dacryostenosis during the years 2004 to 2006 were analysed and the outcomes compared. Surgical success was defined as absence of epiphora and mucous discharge, and of increased tear lake, at the last visit. Results: 68 children (114 eyes) underwent balloon catheter dilatation and 37 children (60 eyes) had probing. Children who had balloon dilatation were significantly older: mean age 55.98±113.6 (range 9.0–728.0) months as opposed to 18.5±6.5 (range 7.0–60.0) months, p<0.01). After a mean follow-up time of 15.4 (range 4–32) months, 102 of 114 eyes were defined as successfully treated following balloon catheter dilatation (89.5% success rate) compared with 52 of 60 eyes following probing (86.7% success rate, p=0.581). Five of six patients (80%) in which the #00 probe could only hardly be inserted into the nasolacrimal duct because of firm bone resistance failed in the probing group, as opposed to only 2/10 (20%) in the balloon catheter group (p=0.03). Conclusion: Children who had balloon catheter dilatation had a slightly better success rate than those who had probing; however, this difference was statistically significant only for patients who had a relatively narrow nasolacrimal bone duct.